2013
DOI: 10.1088/0963-0252/22/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Mackenzie's Demon with instabilities

Abstract: MacKenzie's Maxwell Demon, consisting of positively biased thin wires, heats plasma electrons without significantly affecting the plasma potential. Experiments were performed on the Maxwell Demon in a multi-dipole confined filament discharge. It is shown that given adequate bias, the Demon reduces a bi-Maxwellian electron distribution function to a single Maxwellian electron distribution function. It is shown that a small planar electrode can perform identical heating as the Demon, provided that the electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 18 publications
4
54
1
Order By: Relevance
“…Measurements of the plasma potential and plasma electron temperature were made in the afterglow of a capacitively coupled RF plasma. The slow-sweep probe method [26][27][28] was used in conjunction with the inflection point in the limit of zero emission emissive probe technique 22 to obtain emissive probe I-V traces as a function of time. This is the first time that the inflection point technique was used to make time-resolved plasma potential measurements, a great asset for this method, which is the most accurate of the emissive probe techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the plasma potential and plasma electron temperature were made in the afterglow of a capacitively coupled RF plasma. The slow-sweep probe method [26][27][28] was used in conjunction with the inflection point in the limit of zero emission emissive probe technique 22 to obtain emissive probe I-V traces as a function of time. This is the first time that the inflection point technique was used to make time-resolved plasma potential measurements, a great asset for this method, which is the most accurate of the emissive probe techniques.…”
Section: Discussionmentioning
confidence: 99%
“…If, however, the temporal response being measured is periodic, the slow-sweep probe method has good accuracy with a simpler setup. [26][27][28] To execute this method, the probe is biased at a constant potential and current is measured as a function of time. That procedure is performed for a range of bias voltages, and by transposing the data, probe current versus bias voltage at various times can be obtained.…”
Section: Slow-sweep Probe Methodsmentioning
confidence: 99%
“…In MacKenzie's work, it was argued that a thin positively biased wire preferentially collects low energy electrons because of orbital motion effects, leading to an effective heating effect [50]. However, it was also shown that a biased planar electrode leads to essentially the same result due to the mechanism described above [51].…”
Section: Global Non-ambipolar Flowmentioning
confidence: 99%
“…Yip and Hershkowitz [51] presented a model for the oscillation period based on a rate equation for electron generation and loss. The model was able to describe the qualitative features of their experiment, where fireballs formed near a biased wire array.…”
Section: Hysteresismentioning
confidence: 99%
“…Combining this with the steady-state Langmuir condition of Eq. An interesting observation from experiments is that increasing the size of the electrode decreases the critical bias [89,2]. Eq.…”
Section: Anode Spot Onsetmentioning
confidence: 99%